Caracterización y propuesta técnica de la acuacultura en la zona de monteverde - playa rosada, provincia de Santa Elena - López, Fernando (2009)
The communes of Palmar and Monteverde belonge to the province of Santa Elena, those communities are dedicad principally to the gillnet fishing and they also have developed the acuiculture for laboratories and shrimp farms. Palmar and Monteverde zones, due to their topographic and climatic characteristics and of being sea side coast have allowed that these sectors should develop acuiculture activities based principally producing shrimp larvas of white shrimp (L. vannamei) species. Based of the surveys, it was possible to know the methodologies and intensities of the farms as laboratories than shrimp farms. The results of the surveys show that in the zone nauplio's study the density of sowing is 220 millions for every month in Monteverde and 93 millions in Palmar which it gives a density of total sowing of 313 millions with percentages of survivals of 65.33in the whole cycle. It is necessary to emphasize that these zone only is dedicated to increase the weight of nauplios and these laboratories according to the classification of Acuiculture's Subsecretary are denominated as semicultivate larviculture. They realize only the phase of larviculture. In the case of shrimp farms located in palmar, they are handle an extensive system, and the productions per hectares are 1000-1100 lb. /ha approximately, obtainins an average weight of 11-15 grs. These low yield per crops productivity, depend for the high salinity that exist in these zones. It tried to introduce P. stylirostri species but it was selected by the low productivity